PERFORMANCE ANALYSIS OF FLY ASH TO PREVENT ACID MINE DRAINAGE FORMATION IN COVER PILES (SIMULATION WITH LABORATORY TEST COLUMNS) - Rifqi Rafif Asidiqi, M.
Acid mine drainage (AMD) Is formed when sulfide minerals oxidize with water and air. AAT that has entered the environment can damage agquatle ecosystems due 1o its low pH and high concentratlon of dissolved metals, To prevent the formation 0f AAT, rocks containing sulfide minerals (Potentlal Acld Forming/PAF) are coated with materials that do not contain sulfide minerals (Non-Acid Forming/NAF) 10 prevent oxidatlon. Overcoming the scarcity of NAF materlals in the field, fly ash Srom coal combustion residues In steam power plants can be used as an alternative coating material and mixing materlal. The purpose of this study was 10 determine the performance of fly ash as a coating material and blending material using laboratory test columns in preventing the Jormation 0f AAT. The test column was conducted on a laboratory scale with a weight ratio of PAF 1o fly ash of 1:1, 1:1.5, 1:2 both using the coating method and the mixing method. The results showed that the laboratory test column with the coating method has not been able to raise the pH of the leachate water above 6 where the pH of the leachate water with the coating method has a value between 3.72 - 5.47. While in the mixing method the pH value obtained has a value between 8.07 - 8.33. From the physical parameters, it can be seen that the use of the blending method is better because it can raise the average pH 1o 8. When viewed from the chemical parameters, the blending method Is also better in reducing the value 0f heavy metals Fe to below 0.01 mg/l and Mn to below 2. So that the more effective method in preventing acid mine drainage Is the blending method.